2020
DOI: 10.1155/2020/9834813
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Improves Deoxynivalenol-Induced Inflammatory Response and Intestinal Mucosal Damage in Piglets

Abstract: We investigated the effects of rapamycin (RAPA) and chloroquine (CQ) in supporting growth performance and the intestinal mucosal barrier in response to deoxynivalenol (DON) in piglets. A total of 32 healthy weaned piglets (bodyweight 7.10±0.58 kg) were divided into four groups and treated daily with RAPA (1 mg/kg BW), CQ (10 mg/kg BW), or a control volume of normal saline (two groups) until the end of the experiment. After feeding a basal diet for seven days, three groups were then switched to mildewed feed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…In the present paper, the plasma concentrations of DAO and D-lactate were significant increased after piglets ingested DON-contaminated diet, indicating impaired intestinal barrier function. Similar findings were observed by other researchers [ 33 , 34 ]. Remarkably, supplementation of LGG into the DON-contaminated diet had lower plasma concentrations of D-lactate than that in the DON group and had no significant difference with CON group.…”
Section: Discussionsupporting
confidence: 93%
“…In the present paper, the plasma concentrations of DAO and D-lactate were significant increased after piglets ingested DON-contaminated diet, indicating impaired intestinal barrier function. Similar findings were observed by other researchers [ 33 , 34 ]. Remarkably, supplementation of LGG into the DON-contaminated diet had lower plasma concentrations of D-lactate than that in the DON group and had no significant difference with CON group.…”
Section: Discussionsupporting
confidence: 93%
“…As we expected, RAPA alleviated inflammatory injury and downregulated the expressions of pyroptosis-related genes (NLRP3, ASC, caspase-1, and GSDMD) induced by FB 1 exposure in vivo and in vitro. Consistent with numerous reports, we suggested that promoting autophagy can inhibit the pyroptosis pathway and reduce inflammation. However, it has also been manifested that autophagy can promote the activation of NLRP3 inflammasome and the release of IL-1β, which may be attributed to the abnormal secretion pathways of inflammatory factors or the failure of autophagy to protect against pathogen-induced acute cellular stress.…”
Section: Discussionsupporting
confidence: 92%
“…A DON-contaminated diet usually affects growth performance by reducing the feed intake of piglets [30,31]. RES is a natural polyphenol belonging to the phytoalexin family.…”
Section: Discussionmentioning
confidence: 99%